Isolation, Characterisation and in silico Studies of Bioactive Terpenoid and Flavonoid from the Seeds of Mucuna pruriens - Sutradhar, Ranajit Kumar; Ahmed, Pair; Hossain, Md. Sakhaoyat; Islam, Md. Nazrul; Hossain, Md. Emdad (Asian Journal of Chemistry, 2026)
In this work, new bioactive terpenoids (1-2) and flavonoid (3) have been isolated from the chloroform extract of the seeds of Mucuna pruriens. The structures of the isolated compounds were established by spectroscopic analysis. In vitro antibacterial and antifungal activities of these compounds have been studied. Compound 2 showed the highest inhibition value (16.0 ± 0.5 mm) against S. aureus and (19.3 ± 0.6 mm) against B. subtilis. Compound 2 also exhibited significant antifungal activities with inhibition value (16.0 ± 0.6) mm and (6.0 ± 1.0) mm against T. harzianum and A. niger, respectively. Molecular docking studies and ADME prediction of the compounds were performed. Compound 2 showed good binding affinity ranging between -7.5 to -7.6 kcal/mol with targeted receptors.